Effect of Probiotics Derived from Lactobacillus DH42 as an Alternative to Antibiotics on the Growth Performance, Gut Health, and Immune Response in Broiler Chickens - Prasad Mandal, Guru; Mandal, Surojit; Mandal, Samiran; Samanta, Indranil; Soren, Stephen (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to assess the impact of dietary supplementation with a probiotic (Lactobacillus DH42) on the growth performance,  carcass traits, blood biochemical profile, gut microbiome, gut morphology, and immune response of broiler chickens. A total of 162  day-old mixed sex Vencobb 400 broiler chicks were randomly assigned to three dietary groups, each with six replicated pens (n=6),  containing nine broiler chickens: 1) basal diet without any growth promoter (CON), 2) basal diet with antibiotic (Bacitracin methylene  disalicylate - BMD) at 500 g/ton feed (AGP), and 3) basal diet with probiotic (Lactobacillus DH42) at 1 mL/bird in drinking water (PRO).  Body weight, feed intake, and FCR were monitored weekly for 35 days. Blood biochemistry and immune response were evaluated at  day 28 and 35 of the trial. Carcass traits, gut microbiome, and gut morphology were assessed at the end of the trial. The results indicated  that PRO significantly increased final body weight, average daily gain and improved FCR compared to the control group (p
Keywords: Broiler chicken; Growth performance; Gut microbiota; Immune response